Tratamento da endometriose experimental: a talidomida produz efeito antivasogênico satisfatório? - LIMA, Rafael de Abreu (2023)
Endometriosis is a chronic and debilitating disease associated with pelvic pain and infertility affecting women in the reproductive phase. In addition to the diagnosis being delayed in most cases, clinical treatments are not as effective, as they do not definitively treat. The pathogenesis of endometriosis is similar to that of tumors, the process of angiogenesis is quite evident, mainly with the presence of proteins that stimulate the proliferation of endothelial cells, such as vascular endothelial growth factor (VEGF) and fibroblast growth factor (FCFβ). New treatment strategies have been researched, however, contested. In this context, thalidomide reappears as a pharmacological treatment modality and it can be hypothesized that in adjusted doses, it can produce a therapeutic effect. The objective of this work was to evaluate the antivasogenic and healing effects of thalidomide in the experimental model of endometriosis in rats. Thirty-six female Wistar rats were used, which were submitted to the experimental protocol of endometrial autotransplantation. After diagnosis of endometriosis, the animals were divided into 6 groups: Group A: sham, Group B: negative control, Groups treated with thalidomide at different doses (C: 25mg/kg, D: 50mg/kg and E: 100mg/kg) and Group F: treated with leuprolide (1mg/kg). After 21 days of treatment, the animals were euthanized and the liver, kidney and uterine horns were collected for immunohistochemical (Anti-VEGF) and histological (fibroblasts and toxicity) evaluation. The results demonstrate that the rats treated with thalidomide in groups D (pvalue 0.014) and E (pvalue 0.017) and leuprolide (pvalue 0.001) had the volumes of the endometriotic implants inhibited, when compared to the other groups. Histologically, there were decreases in VEGF and FCFβ expression in groups D, E and F. It was also evidenced, morphological alterations in the hepatic parenchyma of the groups D, E and F. It is concluted, for the model proposed in this research, that thalidomide provides volumetric and histopathological recovery in implants, especially in groups treated with doses of 50 and 100 mg/kg, producing a satisfactory antivasogenic and healing effect, however, there are indications of lesions in the hepatic parenchyma of these groups. It is suggested that thalidomide may be effective in the treatment of endometriosis.